Accounting for the spouse when measuring inequality of opportunity - Andreas Peichl; Martin Ungerer (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Existing literature on inequality of opportunity (IOp) has failed to address the question as to how the circumstances and choices of spouses in a couple should be treated. By omitting information relevant to the spouse in IOp estimations, the implicit assumption was full responsibility for the partner's income, effort and circumstance variables. In this paper, we discuss whether or not the partner's characteristics should be treated as responsibility factors. Using German micro data, we analyze empirically, how IOp estimates are affected when a partner's circumstance or effort variables are included as own circumstances in the analysis. Our analysis indicates that including spouse's variables can increase IOp measures by more than 20 (35) percent for gross (net) earnings. The less the responsibility assumed for the partner's variables, the higher the IOp estimate.
Keywords: D63; H2; J62; J7; 330; Equality of Opportunity; Earnings Inequality; Couple; Family Background; Assortative Mating